Halotolerant PGPR Stenotrophomonas maltophilia BJ01 Induces Salt Tolerance by Modulating Physiology and Biochemical Activities of Arachis hypogaea - Alexander, Ankita; Singh, Vijay K.; Mishra, Avinash (Frontiers in Microbiology, 2020)
Arachis hypogaea (Peanut) is one of the most important cash crops grown for food and oil production. Salinity is a major constrain for loss of peanut productivity, and halotolerant plant growth promoting bacterium not only enhances plant-growth but also provides resistance against salt stress. The potential of halotolerant bacterium Stenotrophomonas maltophilia BJ01 isolated from saline-soil was explored to enhance the growth of peanut plants under salt stress conditions. Interaction of S. maltophilia enhances the growth of the peanut plants and protects photosynthetic pigments under salt stress. It was observed that the physiology of peanut plants was modulated during interaction of S. maltophilia, and electrolyte leakage, lipid peroxidation, and H2O2 content reduced in plants, co-cultivated with PGPR under normal or salt stress conditions compared to the corresponding control plants. The growth hormone auxin and osmoprotectants (proline and total amino acids) were enhanced in plants co-cultivated with PGPR. Overall, these results indicate the beneficial effect of S. maltophilia on peanut plants under salt stress conditions. Previously, it was demonstrated that S. maltophilia supports peanut plants to grow under N2 deficit conditions. In conclusion, bacterium S. maltophilia could be explored further as an efficient PGPR for growing agricultural crops under salt and N2 deficit conditions. However, a detailed agronomic study would be needed to ascertain its commercial role.